2009
DOI: 10.1098/rspb.2009.1631
|View full text |Cite
|
Sign up to set email alerts
|

Varying responses of insect herbivores to altered plant chemistry under organic and conventional treatments

Abstract: The hypothesis that plants supplied with organic fertilizers are better defended against insect herbivores than those supplied with synthetic fertilizers was tested over two field seasons. Organic and synthetic fertilizer treatments at two nitrogen concentrations were supplied to Brassica plants, and their effects on the abundance of herbivore species and plant chemistry were assessed. The organic treatments also differed in fertilizer type: a green manure was used for the low-nitrogen treatment, while the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 39 publications
2
53
5
Order By: Relevance
“…provide little support for a consistent direct effect of fertilizer type on herbivore populations (see also [21]), but a release from competition on plants supplied with synthetic fertilizers might indirectly allow greater population growth under conventional agricultural practices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…provide little support for a consistent direct effect of fertilizer type on herbivore populations (see also [21]), but a release from competition on plants supplied with synthetic fertilizers might indirectly allow greater population growth under conventional agricultural practices.…”
Section: Discussionmentioning
confidence: 99%
“…pekinensis cv Wong Bok) for several generations under the same environmental conditions as detailed above [30]. The infestation sequence (B. brassicae before P. xylostella) was chosen to mimic the order of arrival of these species on UK Brassica plants [21].…”
Section: (A) Experimental Design and Plant Cultivationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recently GSLs have been reported to be involved in mitigating cancer ((Beecher, 1994;Williamson et al, 1998;Das et al, 2000;Hayes et al, 2008) and consumption of large amounts of vegetables especially broccoli, Brussels sprout and cabbage is being encouraged. Staley et al (2010) reported that GSLs in cabbage (Brassica oleracea var capitata) were three times when grown on organic manure than when it was grown on chemical fertilizers. He also reported that the content of glubrassicin was much more than sinigrin.…”
Section: Glucisinolates (Gsls)mentioning
confidence: 99%